Main Neurosurgical Pathologies in Benin Republic... - GANDAHO, HUGUES JEAN-THIERRY; MADOUGOU, SOUMAÏLA; HOUINSOU, ISAAC HANS; djrolo, gauthier; zevounou, Audrey; ADELEYE, AMOS (My University, 2016)
Background: Benin republic is a very low‑income French‑speaking country in West Africa The development of Neurosurgery in the Republic of Benin took off with the arrival of the first Beninese neurosurgeons in the year 2003. Aims: This study aims to evaluate patients’ attendance in a public neurosurgical center, and appreciate populations’ affordability to a new specialty. Settings and Design: In the year 2004, the Benin Armed Forces established the first Department of Neurosurgery in the Nation’s Military Teaching Hospital. From the public authorities, that was a proof of motivation to develop this specialty in the Benin Republic. Materials and Methods: A retrospective cross‑sectional survey (September 2003 to December 2009) of the total neurosurgical patient population managed in a public pioneer hospital in a developing country. Statistical Analysis Used: Data were captured and analyzed with the SPSS software (SPSS Inc., Chicago, IL, USA) and presented in descriptive statistics such as frequencies and proportions. Results: 2908 new patients, civilians, and militaries were registered. The surgical treatment was offered adult (86%) as well as pediatric (14%) patients. Spinal degenerative diseases (52.1%) were the most common pathology; neurotraumatology emergency cases (8.4%) appeared low in representation. Three‑quarters of patients experienced financial difficulties to procure the required radiologic investigations and although 609 (20.94%) benefited from surgery, most patients could not pay for the surgical operations as well as the perioperative care. Conclusions: In spite of the great constraints of this country’s privately‑funded health‑care delivery system on the affordability of neurosurgical treatment for the average Beninese, this study demonstrates a globally increasing attendance of the department.
Keywords: Benin Republic; disease burdens; low‑resource neurosurgical practice; neurosurgery; socioeconomics